Culture of dialogue between beliefs and practices among young people - Yunis, Ghada Mohammed Ahmed (Arab Journal for Sciences and Research Publishing, 2015)
The culture of dialogue consists of two main parallel dimensions: 1- Beliefs, convictions and principles: These include: - Belief in dialogue is a means of communication between people, mutual respect for the other party and faith in the value of his opinion, belief in the right of others to express their opinion. 2 - The actual practices of dialogue: through the practice of dialogue with others, listening to others when they raise their views, the ethics of dialogue and respect the right of others to express their views. In terms of practical reality, we find that the culture of dialogue in Egyptian society stands at the belief that there is a firm belief among young people in the importance of dialogue and its role in the progress of societies, but in practice we find a conflict between saying and work and finding rejection of the other and accusing him of conspiracy and betrayal. The problem of this study and its importance is determined in an attempt to identify the culture of dialogue between the beliefs and practices of young people in Alexandria and the extent to which young people believe in the importance of dialogue in supporting the cohesion of the youth. Combines and the extent of his belief in the right of difference and acceptance of pluralism in the light of the basic principles of citizenship. With reference to the theoretical heritage, we find that the theoretical heritage was not exposed to the culture of dialogue among young people, but rather focused on dialogue in Islam, family dialogue, intercultural dialogue and other subjects that did not deal with the relation between thought and belief and practice.